Evaluation of recombinant Cryptosporidium hominis GP60 protein and anti-GP60 chicken polyclonal IgY for research and diagnostic purposes - Miura,Valéria Chamas (2017)
Abstract In this study, a method for expressing Cryptosporidium hominis GP60 glycoprotein in Escherichia coli for production of polyclonal anti-GP60 IgY in chickens was developed aiming future studies concerning the diagnosis, prevention and treatment of cryptosporidiosis. The full-length nucleotide sequence of the C. hominis gp60 gene was codon-optimized for expression in E. coli and was synthesized in pET28-a vector. Subcloning was performed on several different strains of BL21 E. coli. Temperature, time and inducer IPTG concentration assays were also performed and analyzed using SDS-PAGE. The optimal conditions were observed at a temperature of 37 °C, with overnight incubation and 1 mM of IPTG. Purification was performed by means of affinity chromatography using the AKTA Pure chromatography system and the Hi-Trap™ HP column (GE Healthcare). The recombinant protein GP60 (rGP60) thus generated was used to immunize laying hens owing the production of polyclonal IgY. Western blot and indirect immunofluorescence showed that the polyclonal antibody was capable of binding to rGP60 and to Cryptosporidium parvum sporozoites, respectively. The rGP60 and the IgY anti-rGP60 generated in this study may be used as templates for research and for the development of diagnostic methods for cryptosporidiosis.